PENERAPAN MODEL PEMBELAJARAN STUDENT TEAMS ACHIEVEMENT DIVISIONS BERBANTUAN MEDIA ULAR TANGGA UNTUK MENINGKATKAN HASIL BELAJAR IPS KELAS V - Tito Arizal Bintang; Fine Reffiane; Ikha Listyarini; Sumiyatun (STKIP Subang, 2023)
This study aims to improve the learning outcomes of fifth grade students in social sciences by applying the STAD (Student Teams Achievement Divisions) learning model assisted by Snakes and Ladders media. This research uses Classroom Action Research (CAR), which lasts for two cycles. The stages of implementing this research include planning, implementing, observing, and reflecting. The subjects in this study were fifth grade students at SDN Peterongan Semarang in the 2023–2024 academic year, totaling 26 students as recipients of research actions, while researchers who were given the action were researchers together with class V homeroom teachers. Data collection techniques used observation techniques, interviews, learning outcomes for each cycle, and documentation. The data analysis used in this research includes quantitative and qualitative data analysis. The results of this study indicate an increase in student learning outcomes in social studies subjects in each cycle. In the pre-cycle stage, the average learning completeness was 42.3%; in the first cycle, the average learning mastery was 80.8%; and in the second cycle, there was an increase in learning outcomes again, with an average learning completeness of 92.3%. From these data, it can be concluded that student learning outcomes by applying the STAD learning model assisted by snakes and ladders media in social studies class V starting from the pre-cycle, cycle I, and cycle II have increased.